Gestational diabetes mellitus-induced milk fat globule membrane protein changes of human mature milk based on tandem mass tag proteomic analysis - Ye Tao; Qingcheng Wang; Min Xiao; Haihong Li; Haifeng Wang; Zhujun Mao; Lai Zhang; XiaoLi Zhou; Huijuan Yang; Qing Shen (Journal of Dairy Science)
ABSTRACT: Breastfeeding by mothers with gestational diabetes mellitus (GDM) has been shown to reduce maternal insulin demands and diminish the risks of diabetes in infants, leading to improved long-term health outcomes. Milk fat globule membrane (MFGM) proteins play a crucial role in influencing the immunity and cognitive development of infants. Understanding the alterations in MFGM proteins in breast milk from mothers with GDM is essential for enhancing their self-efficacy and increase breastfeeding rates. The objective of this study is to investigate and compare MFGM proteins in milk from mothers with and without GDM based on tandem mass tag (TMT) labeling and liquid chromatography–tandem MS techniques. A total of 5,402 proteins were identified, including 4 upregulated proteins and 24 downregulated proteins. These significantly altered proteins were found to be associated with human diseases, cellular processes, and metabolism pathways. Additionally, the oxidative phosphorylation pathway emerged as the predominant pathway through Gene Set Enrichment Analysis involving all genes.